Crowding can impact both low and high contrast visual acuity measurements - Pluháček, František; Siderov, John; Macháčová, Ivana (Scientific reports, 2022)
The adverse impact of adjacent contours on letter visual acuity is known as crowding but there is conflicting evidence that foveal crowding may be reduced or disappears under low contrast conditions. Potential differences in foveal crowding with contrast on clinical measurements of visual acuity, including test-retest repeatability, were assessed. Visual acuity was measured at the fovea on adult participants with normal vision under three different contrast levels (- 90, - 10 and - 5%). Three rows of 5 letters, each row differing in size by 0.05 logarithm of the minimum angle of resolution (logMAR) from largest to smallest were displayed at the center of a monitor. Crowding was varied by varying the separation between horizontally adjacent letters from 100% optotype size to 50%, 20% and 10% optotype size. Inter-row spacing was proportional to optotype size. Observers read the letters on the middle row only. Measurements continued by reducing the size of the letters until 3 or more errors were made and were repeated on two separate days. Visual acuity worsened as both letter contrast decreased and inter-optotype separation reduced (expressed as a percentage of letter width). When expressed in minutes of arc of separation the impact of crowding was the same across all contrasts. Crowding occurs for both high and low contrast charts and should be considered when assessing low contrast visual acuity. Test-retest repeatability showed little or no dependence on either contrast or inter-optotype separation.
Keywords: dospělí; Visual Acuity; Adult; lidé; fovea centralis; zraková ostrost; Humans; Fovea Centralis